The impact of squatter settlement in Greater Breyten Urban Community: A case study of Kwa-Zanele Township In Mpumalanga Province - Twala, Mandla Alfred; Twala, Boniswa Charlotte (Technium Social Sciences Journal, 2022)
This study investigated the attitudes of the permanent residents and the squatter-settlements regarding the existence of crime, and the socio-environmental problems experienced by the permanent residents of Greater Breyten Urban Community due to the existence of the squatters in their areas. This growth of squatter settlements, informal settlements, slums along the formal settlement and or urban areas is a global phenomenon. The research design in this study involved a descriptive design which reveals potential relationships between variables. According to the study, the researcher was describing the attitude and impact of quarters on the social environment of the Greater Breyten area. Data was also analyzed using frequencies and percentages. The findings revealed that there are no significant differences between the attitudes of the permanent residents and those of the squatter-settlements regarding the existence of crime. Besides, the socio-environmental problems, the results indicated that the conditions of squatters are poor and unhealthy for human habitation. Considering the findings of the study, the researcher proposed that there be a multi-disciplinary approach to present and provide resources to address the problem of squatter-settlement.